Combining Photothermal Therapy with A Nanohybrid-Based Drug Delivery Strategy for Slow-Released Doxorubicin: A Treatment for Hepatocellular Carcinoma - Muhammad Habiburrahman; Afid Brilliana Putra; Muhammad Ilham Dhiya Rakasiwi (Indonesian Journal of Cancer, 2023)
Background: Hepatocellular carcinoma (HCC) is the fifth most common malignancy in the world. Surgical intervention remains the primary treatment option for resectable liver cancer. However, the low curative resection ratio, high metastatic ratio, and risk of recurrence make this treatment less than ideal. Additionally, the choice of liver transplantation is limited by the availability of donors. This literature review aimed to discuss the combination strategy of photothermal therapy and nanohybrid-based chemotherapy delivery, which are expected to address the challenges in HCC treatment. Methods: We conducted literature searches in Pubmed, Scopus, ProQuest, and Google Scholar using combined keywords such as “hepatocellular carcinoma”, “polyethylene glycol”, “doxorubicin”, “mesoporous silica”, “CuS”, “nanoparticle”, and “photothermal therapy”. Based on the assessment of validity and applicability aspects using modified Oxford CEBM (Center for Evidence-Based Management) and OHAT (Office of Health Assessment and Translation) checklist tools for preclinical studies, all the selected studies fulfilled the eligibility criteria. Results: Photothermal therapy promotes necrosis and apoptosis of HCC cells by ‘heating’ the cancer cells. Meanwhile, the chemotherapy agent doxorubicin, modified with mesoporous silica nanohybrids and encapsulated copper sulfate polyethylene glycol (PEG-DOX-MSN-CuS), enhances the efficiency and duration of drug circulation in the blood, reduces drug clearance, and minimizes retention by the reticuloendothelial system. By utilizing near-infrared light induction from photothermal therapy, doxorubicin can be slowly released, leading to significantly improved effectiveness. In vitro studies have demonstrated that this this combination strategy achieves over 90% HCC cell death at a chemotherapy concentration of 80 µg/mL, in conjunction with near-infrared light induction. The optimal release time for doxorubicin was recored at a concise 20 minutes. Conclusions: Given the numerous benefits associated with this combination of strategies, photothermal therapy using PEG-DOX-MSN-CuS holds significant expected to be a promising treatment for HCC.